Isomorphic Diffusionin Public Sector: Focus on China - Cheng CHEN; Shangxin CHI (Transylvanian Review of Administrative Sciences, 2017)
Based on widely ranged theoretical discussion of isomorphic diffusion, this article traces the process of isomorphism in the context of public service center diffusion in China and discovers relationships between isomorphism and distance within different time and space. With data for a sample of 238 prefecture level cities collected from China, the authors aim to explore the correlation between isomorphism diffusion and spatial distance. The results of the analysis suggest that local governments will be at a disadvantage if these are stated in a further location when isomorphic diffusion takes place. Moreover, the correlation between isomorphic diffusion and spatial distance varies according to the different phases of the diffusion process. The effect of geographical distance is initially strong in the growth period, but weakens later. The results will build bridges on isomorphic and geographical distance within diverse time and space in China, and have implications both theoretically and practically.